10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Conventional tribromoethanol anesthesia is compromised by solvent-related toxicity, limiting its utility in prolonged experimental protocols. We hypothesized that reformulation with 1,2-propanediol could improve its biosafety while revealing its potential mechanism of action in the central nervous system. METHODS: In vivo biocompatibility was evaluated using OECD-standard irritation models, while anesthetic efficacy was quantitatively determined via the up-down sequential allocation method, complemented by tail-immersion and writhing tests to characterize antinociceptive effects. Moreover, physiological stability was monitored using non-invasive tail-cuff plethysmography and rectal thermometry for cardiovascular and core temperature assessment. In addition, subacute toxicity was assessed through repeated dosing, and MRI for neurostructural integrity. Finally, cognitive function and mechanisms were probed via the Morris water maze, molecular docking, region-specific protein expression, and real-time cerebral oxygen saturation mapping using photoacoustic imaging. RESULTS: The 1,2-propanediol formulation markedly reduced local tissue irritation and improved pulse-rate, blood-pressure, thermoregulatory, and repeated-dosing survival profiles compared with the conventional 2-methyl-2-butanol formulation. TBE/PG exhibited dose-dependent anesthetic efficacy without significant strain- or sex-associated differences. Repeated administration induced transient spatial learning impairment and reduced cerebral oxygen saturation; these effects were largely reversible after drug withdrawal and retraining. Molecular docking and regional protein profiling identified GABRA1, which was enriched in the pons, as a candidate mechanistic correlate of TBE-induced anesthesia. CONCLUSIONS: This study establishes a biocompatible TBE formulation as a superior injectable anesthetic with enhanced safety and reversible cognitive effects. The results pinpoint pontine GABRA1 targeting as a novel pathway for TBE-induced anesthesia, providing a robust framework for refining preclinical sedation protocols and future neurotoxicological evaluations.